Penerapan Prinsip Kekeluargaan dan Kegotongroyongan dalam Pengelolaan Badan Usaha Milik Desa pada Masa Pandemi - Wahyu Budi Utama; Aniek Juliarini (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to describe how the application of the principle of kinship and mutual cooperation in Village Owned Enterprises (BUM Desa) during the Covid-19 pandemic. Method: This study uses a qualitative-descriptive method. Data collection techniques by observing objects as full observers, face-to-face interviews, and collecting documents. The case study research method was chosen as the research method. The research location is BUM Desa Karya Lestari Manunggal which is located in Kemasan Village, Sawit District, Boyolali Regency. The data analysis used is data reduction, data presentation, and making conclusions. Results: Most of the BUM Desa management practices carried out by operational implementers have complied with the principles of kinship and mutual cooperation, except for professional principles which have not been fully implemented. Conclusions: The conclusion obtained is that although the management of BUM Desa has been carried out quite well by operational implementers, it still has problems due to pandemic which has caused the closure of business units that manage water tourism.